Esperienze di gestione in una biblioteca accademica: la Biblioteca di scienze sociali dell'Ateneo fiorentino (2004-2015) - Melani, Chiara; Conigliello, Lucilla (Strumenti per la didattica e la ricerca, 2016)
The volume describes experiences of the first twelve years of the Social Sciences Library of the University of Florence in its new location. We talk about management contexts, organisational structures, analysis, projects, crises and solutions affecting most of the services. Moreover, we also present an approach and a working method. Our need to write stemmed from the impression of having accomplished a phase of our work and of being called to take stock of the situation, giving account of the work done and critically analysing it, in order to be ready to face the new challenges that the future would present, starting from today.